Corporate governance in China : research and evaluation - Li, Wei'an, 1957- (J. Wiley & Sons, 2008)
Great progress has been achieved for the structural reform in China enterprises for the past one and a half decades. Along with the reform, the corporate governance structure has been established accordingly. The Chinese Corporate Governance Index (CCGI?NK) is a useful tool to objectively observe and analyze shareholder behavior, board execution, management incentive and restriction, supervisory committee operation, information disclosure and stakeholders' interest protection, and is helpful in diagnosing issues that may arise during corporate operations. The CCGI?NK provides guidance for improvement of corporate governance, and can be used to enhance the sustainable development of corporations.--Chen Qing-Tai, Vice Director, Economic Committee, National Committee of Chinese People's Political Consultative Conference (CPPCC), Former Vice Director of Development and Research Center of the State Council Dean, Public Administration School of Tsinghua University The phenomenal growth of China's capital markets during the past decade belies the fact that Chinese companies have only gradually adopted modern corporate governance structures. Professor Li's book offers a candid and timely assessment of the quality of the governance mechanisms they employ including the factors that influence their quality and how they relate to subsequent corporate performance. A proper understanding is critical for global investors with an interest in China's markets and for scholars who seek to disentangle corporate governance theory and practice in a fascinating market place. --G. Andrew Karolyi, Charles R. Webb Professor of Finance The Ohio State University Corporate governance is a vital issue that China listing companies and enterprises has to deal with. This book reports an important investigation on the subject of corporate governance. As a major result of the study, a series of governance indices conforming to China's situation were proposed in the book. The author of the book hence received the Award of Outstanding Contribution in Chinese Enterprise Management, and I was very pleased to preside the ceremony to present him with this prestigious award. --Cheng Si-Wei, Vice Chairman of the Standing Committee of National People's Congress, Vice President of Fudan Management Award Foundation Corporate governance issues are important around the world. The ability of a firm to raise capital, to align with partners, and ultimately, to sell products and services to cus ...